The Pragmalinguistic and Sociopragmatic Aspects of English: Applying Analytic Abilities to Foreign Language Teaching (Philologia, 2021)
The current paper provides results of a study that investigated the usage of pragmatics by non-native speakers (NNSs) of English when making e-mail requests. Initial data from the study shows that NNSs differ from native speakers (NSs) in politeness and perlocution (i.e., the effect that an utterance has on its recipient) of their English e-mail requests. The data also show that NNSs and NSs differ in the specific pragmatic strategies related to the structure and content used in their e-mail requests. Additional data from this study indicates that explicit instruction can positively affect the perlocution of NNS e-mail requests and the long-term usage of pragmatic features found in the e-mail messages of NNSs, although the greatest effect is observed in the appropriate usage of structural features. The results of this study support the need for instruction of e-mail pragmatics to second language learners and reveal the possible benefits of such instruction.
Keywords: e-mail requests; non-native speakers (NNSs); pragmatics; perlocution